2016
DOI: 10.1007/s00256-016-2329-3
|View full text |Cite
|
Sign up to set email alerts
|

Lower-limb MRI in the staging and re-staging of osteonecrosis in paediatric patients affected by acute lymphoblastic leukaemia after therapy

Abstract: Our MRI protocol proved to be feasible in evaluating ON in paediatric patients. Studies should be addressed only to symptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
4
9
0
2
Order By: Relevance
“…We reported that non-articular osteonecrosis more common than articular osteonecrosis, which agreed with study done by Ippolito D. et al [11], as their study included 45 patients, 13 cases were negative (29 %), 15 patients with non-articular ON (33 %), 12 patients with articular ON (27 %), 5 patients had ON with deformity (11 %).…”
Section: Discussionsupporting
confidence: 92%
“…We reported that non-articular osteonecrosis more common than articular osteonecrosis, which agreed with study done by Ippolito D. et al [11], as their study included 45 patients, 13 cases were negative (29 %), 15 patients with non-articular ON (33 %), 12 patients with articular ON (27 %), 5 patients had ON with deformity (11 %).…”
Section: Discussionsupporting
confidence: 92%
“…To date, a total of 7 studies have reported on MRI screening for ON in children with ALL (Table 1). 5,[14][15][16][17][18][19] MRI time points differed widely between diagnosis and completion of therapy/follow-up in these studies. There was also significant variation in radiological and clinical classification employed, as well as the number of and time intervals between MRIs, limiting the comparability of these studies considerably.…”
mentioning
confidence: 98%
“…Die Inzidenz der ON bei Kindern und Jugendlichen mit malignen Grunderkrankungen variiert zwischen 1,4 % bis maximal 73,9 % (Lackner et al 2005, Ippolito et al 2016.…”
Section: Inzidenz Symptomatik Und Lokalisationen Der Osteonekrosenunclassified
“…Wie in der vorliegenden Studie fanden auch Ippolito et al bei der Betrachtung von ON in der unteren Extremität keine bevorzugte Lokalisation bezüglich der rechten oder linken Körperseite (Ippolito et al 2016).…”
Section: Allem Beiunclassified